Extraction and purification of solanesol from tobacco (I). Extraction and silica gel column chromatography separation of solanesol - Tang, D.; Zhang, L.; Chena, H.; Liang, Y.; Lub, J.; Liang, H.; Zheng, X.
Solanesol, a main polyprenol occurred in tobacco, has gained the attention of biochemists because of its value as a source of isoprene units for the synthesis of metabolically active quinones and vitamin K analogs. This article deals with extraction and purifyication of solanesol. Ground tobacco leaf was extracted with petroleum ether in 50 .C water bath under reflux for 2 h, and then filtrated, the powder leaf was re-extracted successively with petroleum ether and the extracts were pooled and concentrated to get pasty residue. The residue was saponified and subsequently loaded onto silica gel column chromatography. The chemical was eluted using a binary solvent mixture of petroleum ether.acetone (90:10, v/v)and the eluent was collected by fraction size of 5 ml. Tentative identification was carried out using TLC. The fractions mainly contained solanesol were pooled and dried by rotary evaporation. The yield of solenosol was 0.38
Keywords: SOLANESOL; EXTRACTION; SEPARATION; SILICA GEL COLUMN CHROMATOGRAPHY